Morphometrics of Pampas foxes (Pseudalopex gymnocercus) in the Argentine Pampas - Luengos Vidal, Estela Maris (2009)
The size of a mammal is closely related to and influences virtually every aspect of its biology (McNab 1971, Clutton-Brock and Harvey 1983) from its physiology and behaviour to its life history and ecology (Gehrt and Fritzell 1999). Total mammalian body mass may indicate the condition of individuals (Sweitzer and Berger 1993) and the mean body mass across individuals may indicate the health of a population (Harder and Kirkpatrick 1994, Warrick and Cypher 1999). Therefore, morphological information may be particularly valuable when managing populations. Sexual dimorphism is a frequent source of intra-specific variability, and it should be taken into consideration in population studies. Moderate sexual dimorphism is common among canids, with females on average 3%–4% smaller in linear measurements than males (Hildebrand 1953).